EXPORT-LED GROWTH: TIME SERIES APPROACH ANALYSIS “CASE OF JORDAN, KUWAIT, AND EGYPT “ - Daoud, Hussam-Eldin; Basha, Mazen (European Scientific Journal, ESJ, 2015)
This study examines the export-led growth (ELG) for three Arab countries (Jordan, Kuwait, and Egypt); through cointegration and Granger causality tests. During 1976 to 2013; strong support for a long-run relationship between exports and real output for these countries. There is bidirectional causality between GDP and export for Jordan and unidirectional causality from export to GDP for Kuwait and Egypt. The results suggest that Jordan, Kuwait, and Egypt can expand its limited domestic market by exporting more in order to increase economic growth, and export in Jordan can be promoted by increasing economic growth.